Can Nidogen-1 and Nidogen-2 improve our preoperative cancer detection rate? - Agnieszka Kwiatkowska; Dominika Krawczyk; Krzysztof Kułak (Journal of Pre-Clinical and Clinical Research, 2021)
Introduction and objective Ovarian cancer (OC) is the third most commonly diagnosed gynecological cancer among women worldwide and the second most common in Poland. Early-stage ovarian cancer is still very difficult to diagnose and concerns only about 20–30% of all ovarian cancers. Most cases (approximately 70%) of ovarian cancer are diagnosed at more advanced stages (III and IV). The aim of the review is to bring closer new potential biological markers – Nidogen-1 and Nidogen-2 in the diagnosis of ovarian cancer.